Design, Synthesis of Novel N-Substituted 6α-Piperazinomethyl-Δ4-3,17-diketosteroids and their Antimicrobial Activity Evaluation - Davydova, Nadejda K.; Sergeev, Vladimir N.; Peregudov, Alexander S.; Kuvarina, Anastasia E.; Sadykova, Vera S.; Savinova, Tatiana S. (Current Organic Chemistry, 2023)
This report presents the synthesis of three innovative N-substituted 6α- piperazinomethyl-Δ4-3,17-diketo-steroids via the region-directed three-component condensation method. The compounds were produced from N-substituted piperazine derivatives and androst-4-en-3,17-dione (AD). Comprehensive physicochemical methods of analysis were employed to characterize the synthesized products. The study involved antibacterial testing of the synthesized compounds against Escherichia coli ATCC 25922, Bacillus subtilis ATCC 6633, and Staphylococcus aureus 209P FDA, with a comparison to the amoxicillin/clavulanic acid composition. It further assessed antifungal activity against Aspergillus niger INA 00760, with results compared to amphotericin B and nystatin. Initial assessment of the antibacterial and antifungal activities exhibited by the synthesized compounds suggests that this series of N-substituted 6α-piperazinomethyl-Δ4-3,17-diketo-steroids holds great potential for further biological investigation.
Keywords: antifungal activity